Speech - Bravo, Tobías (1952)
He wanted the Society of Neuro-Psychiatry and Lega Medicine, through its distinguished President Dr. Juan Francisco Valega, in commemoration of the centenary of the birth of Santiago Ramón y Cajal, Histology paramount figure, fair and glory of Spain world, it is I who say a few words on behalf of the many gathered here to continue studies at the Madra country and therefore we had to really approach the person and the environment of the Master.